Longitudinal changes in brain iron quantification biomarkers and their association with clinical severity in parkinson’s disease: a systematic review - Thejas M S; Saikiran Pendem; Arvind N Prabhu; Rajagopal Kadavigere; Priyanka; Abhishek Yadav; Abhijith S (BMC Neurology, 2026)
Abstract Purpose Reliable biomarkers for tracking Parkinson’s disease (PD) progression remain an unmet clinical need. Quantitative susceptibility mapping (QSM), an MRI technique sensitive to iron-related susceptibility changes, has emerged as a promising candidate biomarker; however, longitudinal findings have been limited and inconsistent. This study systematically evaluates longitudinal changes in regional QSM measures and examines their relationship with clinical disease severity, aiming to clarify the utility of QSM as a marker of PD progression. Methods Database searches were conducted across PubMed, Scopus, Web of Science, and Embase to identify relevant longitudinal studies evaluating QSM changes in PD. Studies with repeated MRI assessments and reported associations with clinical outcomes were included. Results Five longitudinal studies evaluating QSM in PD met the inclusion criteria. Follow-up ranged from 18 months to 4 years. Most studies reported increasing QSM values in the SN over time, whereas changes in other regions were inconsistent. Higher QSM values were associated with worse motor severity, as assessed primarily by UPDRS Part III/MDS-UPDRS Part III and Hoehn & Yahr stage, whereas cognitive and other non-motor associations were inconsistent. Conclusion Longitudinal QSM changes in PD appear region-specific, with the most consistent alterations observed in the substantia nigra, particularly the substantia nigra pars reticulata (SNr). QSM shows promise as a non-invasive biomarker for tracking disease progression, especially motor progression.